The making of a Navy SEAL [large type] : my story of surviving the toughest challenge and training the best - Webb, Brandon; Mann, John David (Thorndike Press large print biographies and memoirs., 2016)
Brandon Webb's experiences in the world's most elite sniper corps are the stuff of legend. From his grueling years of training, to combat tours in the Persian Gulf and Afghanistan, to training some of America's finest and deadliest warriors, Webb offers a rare and riveting look at the inner workings of the U.S. military.